System Failure: Why Governments Must Learn to Think Differently - Chapman, Jake (Demos, 2004)
The current model of public policy-making is no longer right for a gov ernment that has set itself the challenge of delivery. Improvements ar e driven by central policy initiatives which assume a direct relations hip between action and outcome - but this is a false assumption. Publi c services are complex adaptive systems which are subject to the law o f unintended consequences, so intervention can make problems worse. Th at is why the carrot-and-stick approach to reform which links increase d funding to tougher performance targets will not succeed in the long run. Renowned systems thinker Jake Chapman describes how government's energetic attempts to force change from the centre are becoming counte r-productive. The alternative is government based on continuous learni ng. This is increasingly important as the impact of communication tech nology and other accelerating social trends offers a moving target for public service reformers. Systems thinking offers a better model for change in complex organisations such as the health service or the rail way network. Case studies provided by the NHS confederation show the u nintended and often bizarre consequences of introducing new policies w ithout considering their impact on the whole system. Since the origina l publication of Systems Failure in 2002, many of its core ideas have been taken on by government. In this second edition, Chapman reflects on the experience of putting systems thinking into practice in public services, and explains why the changes he suggests are more difficult - and more urgent - than expected.